Pollution control and cost analysis of wastewater treatment at industrial parks in Taihu and Haihe water basins, China. (20th January 2018) - Long, Sha; Zhao, Lin; Shi, Tongtong; Li, Jingchen; Yang, Jiangye; Liu, Hongbo; Mao, Guozhu; Qiao, Zhi; Yang, Yongkui
Abstract: It is becoming increasingly important to control the discharge of industrial wastewater from industrial parks in order to reduce water pollution. In this study, a comprehensive investigation of water treatment at industrial parks in two large basins in China was carried out, involving comparative and correlation analysis of wastewater quality, pollutant removal, sludge production and cost. In both basins, the average influent chemical oxygen demand, ammonia, and total nitrogen at the centralized wastewater treatment plants in chemical parks were higher than those in comprehensive parks. Anaerobic-anoxic-oxic and anoxic-oxic were the most widely used treatment processes at both comprehensive and chemical parks in the two basins—similar to municipal wastewater treatment plants in China. The operating costs of centralized wastewater treatment plants in the comprehensive and chemical parks comprised the following components: electricity > labor > chemical costs. Reductions in chemical oxygen demand, ammonia and total nitrogen and total phosphorus in the centralized wastewater treatment plants in the parks led to an average reduction of 28% in total pollutants in municipal and industrial wastewater in the two basins. These results could have supports for the design and optimization of wastewater treatment processes, as well as for evaluation of how centralized wastewater treatment plants can help to control water pollution. Graphical abstract: Image 1 Highlights: Industrial parks in two large Chinese water basins were studied. Centralized water treatment plants greatly reduced water-based pollution. AAO and AO were the most widely used treatment processes in the industrial parks. Water quality and treatment process were similar to the municipal WWTPs. Further evaluation of the chronic effect of industrial parks on waters is needed.